Asymptotic expansions of solutions to singularly perturbed systems - Shchitov, I. N. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
Under the condition that a degenerate system has an exponentially stable integral manifold, an asymptotic expansion of the Cauchy problem that generalizes the well known Vasil'eva expansion is constructed for a perturbed system.